Análisis de la figura “Programa de Clemencia” en derecho de competencia comparado. Parámetros para la aplicación en Ecuador (Tema Central) - Trujillo Viteri, Carlos Alfredo (2016)
The leniency program is an important tool of the competition law in order to punish, discover, and prevent cartel activities. The most important leniency programs of the world are from the United States, USA and the European Union, EU. In both legislations the differences and nuances of the program are clear and deep because of the differences of the objectives of the competition law in the USA and the EU. In this work, the importance of this program in the competition law, the comparison of the USA and de EU programs, and the parameters for its application in Ecuador will be analyzed.